(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The dynamic development of industry and technology and the increased need in the field of wood industry have led to a reduction in the forest fund. The depleted forest fund can not meet the market’s needs because it takes a lot more time to reach full maturity, so there is a reason for commercial timber, which includes paulownia. Paulownia is a wood that has exceptional growth rates and for a short period of time give a large amount of wood. Everything is used from wood. It is used as heating material, erosive protection, industrial wood, honey plant, ecological wood, decorative wood, in animal feed, pharmaceutical industry, etc. Biomass from paulownia is suitable both for silage and for alternative renewable energy sources. One of the most promising applications is bioethanol derived from cellulose. The cultivation and use of paulowane contributes to the maintenance of ecological balance and conservation of nature on our planet. Because of the wide range of applications, the need for paulownia is constantly increasing.